IMPLEMENTASI STANDING STORK TEST SECARA DARING UNTUK MENGUKUR ASPEK KEBUGARAN JASMANI KESEIMBANGAN SISWA SMPN 1 BANGKALAN - Rahardian Kurnia Ardi; Fajar Hidayatullah; Khoirul Anwar (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Physical education is a significant subject for junior high school students that study in theory and practice. However, the COVID-19 pandemic condition requires learning activities performed without direct meetings to avoid virus transmission. One subject that experienced obstacles in the test performance was the Standing Stork Test. It is a balance test on gymnastic subjects to measure students' physical fitness and balance. This study was conducted to analyze the factors that influence the online Standing Stork Test implementation at SMPN 1 Bangkalan. The research was conducted qualitatively and analyzed descriptively by conducting interviews with students who were the object of the test. The population was 56 students of class VII SMPN 1 Bangkalan that practiced the Standing Stork Test online and offline, each of which was carried out on the right leg and left foot, repeated 3 times. The results were then compared in the t-test to formulate a conclusion. The results showed that the Standing Stork test conducted online and offline did not significant difference. This is presumably due to the balance ability of students is not influenced by the location and technique of taking scores but is more influenced by the condition of the student's fitness.